Human D-aspartate Oxidase: A Key Player in D-aspartate Metabolism - Pollegioni, Loredano; Molla, Gianluca; Sacchi, Silvia; Murtas, Giulia (Frontiers in Molecular Biosciences, 2021)
In recent years, the D-enantiomers of amino acids have been recognized as natural molecules present in all kingdoms, playing a variety of biological roles. In humans, d-serine and d-aspartate attracted attention for their presence in the central nervous system. Here, we focus on d-aspartate, which is involved in glutamatergic neurotransmission and the synthesis of various hormones. The biosynthesis of d-aspartate is still obscure, while its degradation is due to the peroxisomal flavin adenine dinucleotide (FAD)-containing enzyme d-aspartate oxidase. d-Aspartate emergence is strictly controlled: levels decrease in brain within the first days of life while increasing in endocrine glands postnatally and through adulthood. The human d-aspartate oxidase (hDASPO) belongs to the d-amino acid oxidase-like family: its tertiary structure closely resembles that of human d-amino acid oxidase (hDAAO), the enzyme that degrades neutral and basic d-amino acids. The structure-function relationships of the physiological isoform of hDASPO (named hDASPO_341) and the regulation of gene expression and distribution and properties of the longer isoform hDASPO_369 have all been recently elucidated. Beyond the substrate preference, hDASPO and hDAAO also differ in kinetic efficiency, FAD-binding affinity, pH profile, and oligomeric state. Such differences suggest that evolution diverged to create two different ways to modulate d-aspartate and d-serine levels in the human brain. Current knowledge about hDASPO is shedding light on the molecular mechanisms underlying the modulation of d-aspartate levels in human tissues and is pushing novel, targeted therapeutic strategies. Now, it has been proposed that dysfunction in NMDA receptor-mediated neurotransmission is caused by disrupted d-aspartate metabolism in the nervous system during the onset of various disorders (such as schizophrenia): the design of suitable hDASPO inhibitors aimed at increasing d-aspartate levels thus represents a novel and useful form of therapy.